New one-line model for shoreline evolution at beaches composed of not cohesive grains of any size - Francone, Antonio; Furgiuele, Franco; Tomasicchio, Giuseppe Roberto; Frega, Ferdinando (My University, 2020)
Over recent decades, efforts have been made to find robust methods for predicting shoreline evolution near to the coastal structures. This requires a rigorous understanding of the key coastal processes that drive sediment transport, and how they are impacted by the presence of structures. Once this understanding is reached, a method for predicting morphological shoreline evolution is required. In this context, numerical modelling plays an important role. A new one-line model for shoreline evolution at beaches composed of not cohesive grains of any size is proposed: the General Shoreline beach (GSb). GSb model is based on the one-line theory, for which it is assumed that the equilibrium beach profile remains unchanged (Dean, 1990), thereby allowing beach change to be described uniquely in terms of the shoreline position. The longshore sediment transport rate is estimated by means of a general formula/procedure (Tomasicchio et al., 1994; Lamberti and Tomasicchio, 1997; Tomasicchio et al., 2013; Tomasicchio et al., 2015) combining an energy flux approach with an empirical/statistical relationship between the waveinduced forcing and the number of moving units. The uniqueness of the proposed new one-line model consists in the possibility to simulate beach change, including the effects of coastal structures (i.e. groynes, detached breakwaters), at a mound composed of not cohesive grains of any size, from sand to rock units. Despite other existing models, the GSb model presents a calibration factor, KGSb solely and it has been calibrated and verified against field and laboratory data on sandy and mixed beach (sand and gravel) referring to simple groyne and detached breakwater (Ming and Chiew, 2000; Hamilton et al., 2001; Martin-Grandes et al., 2009; Medellin et al., 2018;). Optimal values of KGSb, valid for different types of not cohesive grains and coastal structures, have been reported. It is showed that the GSb model can be considered a reliable engineering tool to conduct morphodynamics studies. A demo version of the GSb model, for Mac and Windows systems, has been released for the scientific community and is available at www.scacr.eu.
Dottorato di Ricerca in Ingegneria Civile e Industriale - Ciclo XXXII
Keywords: Shoreline; Grains